Pengaruh Pengelolaan Keuangan Dana Beasiswa Kartu Indonesia Pintar (KIP) Terhadap Kebutuhan Biaya Hidup Mahasiswa Universitas Negeri Medan - Sianturi, Rejosu Vanhot; Karubuy, Yulce Ketrina; Batu, Siska Lumban; Ginting, Suriyani Br (SJEE (Scientific Journals of Economic Education), 2025)
This study aims to explore the management of KIP Kuliah student scholarship funds at Medan State University and its impact on the provision of academic needs and their welfare. The research method used is qualitative with a descriptive approach, involving in-depth interviews with scholarship recipients. Data obtained from the interviews were analyzed to identify key themes related to financial management, challenges faced, and strategies implemented by students in using scholarship funds. The results of the study indicate that the effectiveness of KIP fund use is highly dependent on students' ability to manage their finances. Students who are able to budget and record expenses can better meet their educational and living needs, and reduce the financial burden on their families. In addition, good financial management contributes to increased focus and academic achievement of students. Overall, this study confirms that the KIP Kuliah scholarship not only provides financial support, but also plays an important role in helping students develop financial management skills that are important for their future. These findings are expected to provide insight for related parties in designing more effective support programs for students, as well as increasing awareness of the importance of financial literacy among scholarship recipients.